Rehabilitation Of Fire Damaged Reinforced Concrete Columns Using Ultra High Performance Fibre Reinforced Concrete - Zahid, Mohd Zulham Affandi Mohd (2020)
The aim of this study is to investigate the potential use of UHPFRC as a repair material for fire damaged reinforced concrete (RC) short columns. Previously researchers used Fibre Reinforced Polymer (FRP) to repair fire damaged RC columns but they found that it cannot reinstate the original load carrying capacity of the affected square columns. Moreover, FRP also failed to improve the stiffness of fire damaged square and circular RC columns. UHPFRC has shown an excellent bond strength with fire damaged concrete and its ability to recover the load bearing capacity of the fire damaged RC columns. However, there is no experimental evidence on the effect of UHPFRC layer in enhancing mechanical properties of fire damaged RC column. In this current study, forty four (44) specimens RC short columns were heated at 600oC for two hours and tested under compression load. All the RC short column specimens were tested under uniaxial compression load. Stress and strain were measured and recorded using LVDTs and strain gauges at the critical points. Three variables were considered namely geometry of column (square and circular cross section), thickness of repair material and the amount of fibre in UHPFRC. It was found that the increase of UHPFRC jacket thickness and steel fibre content have significantly improved the load bearing capacity, stiffness and ductility of fire damaged RC square and circular columns. This study proposes to use 20 mm thick UHPFRC jacket with 2% steel fibre to repair fire damaged RC columns. In conclusion, the use of UHPFRC as repair material in jacketing technique is one of effective repair material to retrofit fire damaged RC short columns.